Relevansi Relevansi Antara Profitabilitas, Likuiditas Dan Leverage Terhadap Kebijakan Dividen Pada Indeks LQ 45 Yang Terdaftar Di Bursa Efek Indonesia - Prasetyo, Irvan; Suryandani, Wulan (Universitas Islam Kadiri, 2023)
This research was conducted with the aim of testing and explaining the influence of profitability, liquidity and leverage on dividend policy at LQ 45 companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The type of data used is secondary data from each LQ 45 company obtained from the official website of the Indonesia Stock Exchange via ww.idx.co.id and annual reports. The sampling technique used by researchers was purposive sampling. The number of samples used in the research was 22 LQ 45 companies that issued dividend policies for the 2018-2022 period. The data analysis technique used is multiple linear regression analysis test. The research results show that profitability is significantly positive on dividend policy. Negative liquidity is significant to dividend policy and positive leverage is not significant to dividend policy. Keywords: Profitability, Liquidity, Leverage and Dividend Policy